L’immigration clandestine à Mayotte : un phénomène révélateur de l'incidence des changements climatiques sur la sécurité humaine? - Nadia Wu-Tiu-Yen (Éditions en environnement VertigO, 2015)
The French department of Mayotte located in the heart of Indian Ocean undergoes a high level of migrations from the archipelago of the Comoro Islands. Under the influence of climate changes, this phenomenon may be aggravated which is very curious because every island of the archipelago are facing similar geological and meteorological conditions. Considering the level of vulnerability of theses populations, the human security approach may be a good way to look at this situation.